Postoperative bladder dysfunction and outcomes after minimally invasive extravesical ureteric reimplantation in children using a laparoscopic and a robot‐assisted approach: results of a multicentre international survey. (6th September 2019) - Esposito, Ciro; Varlet, Francois; Riquelme, Mario A.; Fourcade, Laurent; Valla, Jean S.; Ballouhey, Quentin; Scalabre, Aurelien; Escolino, Maria
Abstract : Objectives: To assess and compare postoperative bladder dysfunction rates and outcomes after laparoscopic and robot‐assisted extravesical ureteric reimplantation in children and to identify risk factors associated with bladder dysfunction. Patients and Methods: A total of 151 children underwent minimally invasive extravesical ureteric reimplantation in five international centres of paediatric urology over a 5‐year period (January 2013–January 2018). The children were divided in two groups according to surgical approach: group 1 underwent laporoscopic reimplantation and included 116 children (92 girls and 24 boys with a median age of 4.5 years), while group 2 underwent robot‐assisted reimplantation and included 35 children (29 girls and six boys with a median age of 7.5 years). The two groups were compared with regard to: procedure length; success rate; postoperative complication rate; and postoperative bladder dysfunction rate (acute urinary retention [AUR] and voiding dysfunction). Univariate and multivariate logistic regression analyses were performed to assess predictors of postoperative bladder dysfunction. Factors assessed included age, gender, laterality, duration of procedure, pre‐existing bladder and bowel dysfunction (BBD) and pain control. Results: The mean operating time was significantly longer in group 2 compared with group 1, for both unilateral (159.5 vs 109.5 min) and bilateral procedures (202 vs 132 min; P = 0.001). The success rate was significantly higher in group 2 than in group 1 (100% vs 95.6%; P = 0.001). The overall postoperative bladder dysfunction rate was 8.6% and no significant difference was found between group 1 (6.9%) and group 2 (14.3%; P = 0.17). All AUR cases were managed with short‐term bladder catheterization except for two cases (1.3%) in group 1 that required short‐term suprapubic catheterization. Univariate and multivariate analyses showed that bilateral pathology, pre‐existing BBD and duration of procedure were predictors of postoperative bladder dysfunction ( P = 0.001). Conclusion: Our results confirmed that short‐term bladder dysfunction is a possible complication of extravesical ureteric reimplantation, with no significant difference between the laparoscopic and robot‐assisted approaches. Bladder dysfunction occurred more often after bilateral repairs, but required suprapubic catheterization in only 1.3% of cases. Bilaterality, pre‐existing BBD and duration of surgery were confirmed on univariate and multivariate analyses as predictors of postoperative bladder dysfunction in this series.